THE ISLAMIC WOMEN MOVEMENT FOR SOCIAL WELFARE IN INDONESIA: A STUDY ON WOMENS ORGANIZATION âAISYIYAHâ IN MALANG REGENCY, EAST JAVA - INDONESIA - Sukmana, Oman (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2018)
Aisyiyah is an organization of Islamic womens social movements aimed at improving the social welfare of women in Indonesia. The organization has spread throughout the country at national, provincial, district /city, sub-district, and village levels. This study was undertaken on Aisyiyahof Malang Regency to describe the types of activity performed by the organization and the implementation of the Islamic values in improving the women social welfare. A qualitative research approach was adopted and the data were collected from the interview, documentation, records, and other archival materials available in the organization management office. The results showed that the activities of Aisyiyah organizations at the local level were manifested in the form of various business charities, including (1) Sub-sub- recipient community TB-care; (2) Kindergarten teachers association; (3) Zakat, infaq, and shadaqahinstitute; (4) Economic Business-Cooperative; and (5) Junior high boarding school.The Islamic values underlying the spirit of the movement were the values contained in the Al-Quran, surah of Al-Maun regarding the obligation of Muslims to care for orphans and the poor.